069. Evaluation Quality of Life in Colorectal Cancer Patients After Rectal Resection with Ileostomy - Farishal, Ahmad; Sofii, Imam (JBN (Jurnal Bedah Nasional); Vol 8 No 2 (2024): Proceeding The 2nd National Conference of Indonesia Surgical EducationDO - 10.24843/JBN.2024.v08.is02.p069, 2024)
Background : Colorectal cancer where each person has a risk of 1:23 of colorectal and increases according to lifestyle colorectal is the 3rd highest cancer with a prediction of 3.2 billion new cases by 2040. Surgery in the form of resection with ileostomy is performed in up to 95% of cases of colorectal cancer. Quality of life after surgery with ileostomy can be evaluation with EORTC QLQ-C30 and CR29. Methods : Retrospective method with total sampling for 1 year 2023-2024 conducted at Sardjito Hospital, patient data obtained from medical records, questionnaire evaluation using interviews with inclusion criteria. Results : There were first complaints the patient in the form of 54% of bloody stools with the time of complaints range 6 months to 1 year. While 60% of patients came from hospital referrals using government health insurance. The age range is 58 years and dominated by women with BMI status of underweight patients and low education. Tumor borders at 5-10 cm from the anal verse with 75% performed adjuvant chemotherapy and 87% performed colonoscopy. Stage was predominantly stage 3 and adenocarcinoma cancer type up to 65%. EORTC QLQ-C30 and EORTC QLQ-CR29 evaluation results showed differences in emotional functioning at 6 months (p0.04) and decreased body image at 3 months postoperatively (p0.02). There were differences in global quality of life in parts but none in general (p>0.05). Conclusion: Overall, patients experience changes in emotional function at 6 months post and body image at 3 months postoperatively. overall global quality of life scores are no significant.